1264 A Cross-Sectional Study of Psychological Expectations of Orthognathic Surgery Patients Based on Their Typology. (12th October 2021) - Falinda, D; Tahim, A; Cronin, A; Komath, D; Pabla, R; Mistry, P; Lee, S
Abstract: Aim: Orthognathic surgery corrects craniofacial deformity which compromises breathing or masticatory function. Patients typology influences their expectations for physical and psychological transformation before and after surgery and is an emerging area of research. This study aims to evaluate: 1) subjective expectations and/or perceived outcomes and 2) whether orthognathic surgery meets patients' expectations. Method: A questionnaire-based cross-sectional survey was administered pre- and post-operatively. Patients were classified according to typology, namely metamorphosizers - patients with high expectation of psychological and physical changes, evolvers - opposite of metamorphosizers, pragmatists - low expectation of psychological and high expectation of physical changes, and shedders - opposite of pragmatists. A chi-square test was used to examine whether orthognathic surgery met patients' expectations. Results: A total of 27 patients consisting of 19 pre-operative and 8 post-operative completed the survey over an 11-month study period (females = 11; males = 16; mean age= 22.5 years; range = 17-52). Typologically, metamorphosizers dominated, 48%, followed by shedders, 30%, evolvers, 13% and pragmatists, 9%. This indicates that most patients, 78% (metamorphosizers and shedders) had high expectations of psychological change pre-operatively [X 2 (2, N = 90) = 43.9, p < .0001)] and perceptions of psychological change post-operatively [X 2 (2, N = 90) = 48.8, p < .0001)]. Conclusions: Most patients in this study anticipated and perceived psychological changes after orthognathic surgery. Understanding patient typology may help the orthognathic surgeon understand, address and improve post-operative psychological outcomes in their patients.